CHRISTIAN DIALOGUE AND COOPERATION FOLLOWING ŽELJKO MARDEŠIĆ’S IDEAS (Религиски дијалог и соработка, 2023)
Following the idea of the famous Croatian sociologist Željko Mardešić (JakovJukić), this paper analyzes Mardešić’s vision of Christian dialogue and cooperation in thecontext of contemporary sociology of religion. The presented vision of dialogue and cooperationin relation to various social, cultural, and religious changes calls for expandingthe space for dialogue and cooperation. According to Mardešić, dialogue and cooperationpresuppose the existence of opposite ideas and not necessarily identity; otherwise,they would be reduced to mere confirmation. Thus, dialogue and cooperation observedseparately contain an entire program and are key to the realization of Christianity in thefuture. Željko Mardešić sees the future of Christianity along the lines of the Second VaticanCouncil, which remains the “compass” for the Catholic Church, on four council levels:establishing a dialogue with divided Christians, major world religions, non-believers,and the modern world. Importantly, dialogue and cooperation in the Church representan unavoidable prerequisite to establishing four effective dialogues with the world. Inthis context, the authenticity of Christian dialogue and cooperation, according to ŽeljkoMardešić, can be summed up in a few demanding words: kindness, forgiveness, mercy,service, peace, and the joy of hope. A person – not seen as an object but a subject of experience– is certainly changed by every dialogue because the experience itself is dialogicaland open to cooperation.